Principles of formation of buildings located on the surface of the water - Kornilova A.A., Корнилова А.А.; Dzhambulov A.B., Джамбулов А.Б. (Рroblems of engineering and professional education, 2022)
The article presents the basic principles of environmental design of water-surface buildings. The construction of floating structures shows that they not only have environmental advantages, but also save marine energy resources, which leads to economic benefits.